Estimating Nitrogen Availability of Heat-Dried Biosolids - Craig G. Cogger; Andy I. Bary; Elizabeth A. Myhre (Applied and Environmental Soil Science)
As heat-dried biosolids become more widely produced and marketed, it is important to improve estimates of N availability from these materials. Objectives were to compare plant-available N among three different heat-dried biosolids and determine if current guidelines were adequate for estimating application rates. Heat-dried biosolids were surface applied to tall fescue (Festuca arundinacea Schreb.) in Washington State, USA, and forage yield and N uptake measured for two growing seasons following application. Three rates of urea and a zero-N control were used to calculate N fertilizer efficiency regressions. Application year plant-available N (estimated as urea N equivalent) for two biosolids exceeded 60% of total N applied, while urea N equivalent for the third biosolids was 45%. Residual (second-year) urea N equivalent ranged from 5 to 10%. Guidelines for the Pacific Northwest USA recommend mineralization estimates of 35 to 40% for heat-dried biosolids, but this research shows that some heat-dried materials fall well above that range.